COVID-19 MITIGATION IN BUILT ENVIRONMENTS - AVERTING CONTAMINATION AND REDUCING PROLIFERATION OF VIRAL PANDEMICS - Teo Kok Wei,; Mohd Shahril Abdul Rahman, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The Covid-19 viral pandemic has spread to every corner of the globe, making it one of the greatest disasters in modern history. Stakeholders can avert virus contamination and reduce the proliferation of such pandemics through built environment mediated pathways which will benefit decision-making processes. This paper aims to present the challenges facing built environments, the improvements that can be made and technological advances available to study the approaches required to address the potential for contamination by pandemics such as Covid-19. A comprehensive and detailed review was done determine the challenges facing built environments during pandemics, subsequent improvements to built environments, and technological advances available was done. It was found that compliance to standard operating procedures and design limitations were challenges faced, improvements such as building reforms, post-pandemic office and home designs can be carried out, and technological advances such as construction strategy and digital transformation can be applied. Further research must be carried out as resources and literature pertaining to issues concerning Covid-19 in built environments is still in the infancy period.